Are you “phubbing” me? The Determinants of Phubbing Behavior and Assessment of Measurement Invariance across Sex Differences - Soo Ting T'ng; Khee Hoong Ho; Sew Kim Low (RIMCIS, 2018)
Phubbing behavior is pervasive but the examination of the determinants and measurement invariance remain deficient. The present study aims to investigate: (1) relationships between Big Five personality traits (i.e., open-mindedness, conscientiousness, extraversion, agreeableness, and negative emotionality), coping styles (i.e., problem-focused and emotional-focused), Internet addiction and phubbing behavior; (2) the mediating role of Internet addiction among these relationships; and (3) measurement invariance across sex groups. A total of 405 responses were included in the final analyses. Participants were sampled using a probability-proportionate-to-size (PPS) method. Data were collected using paper-and-pencil survey: Phubbing Scale, Internet Addiction Test, Big Five Inventory, and Simplified Coping Styles Questionnaire. Negative emotionality, open-mindedness, and Internet addiction were the significant determinants of phubbing behavior. Internet addiction partially mediates open-mindedness and phubbing behavior. As for measurement invariance across sex groups, conscientiousness, extraversion, negative emotionality, Internet addiction, and phubbing behavior constructs achieved full measurement invariance. The agreeableness construct showed partial measurement invariance. Three constructs (i.e., open-mindedness, problem-focused and emotional-focused coping) failed to achieve partial measurement invariance, signifying that male and female participants had different interpretations on the items of these constructs. This pervasive culture could be gradually weakened if in-person interaction is intensely promoted.